Hubungan Pola Asuh Orang Tua dan Kemandirian Anak Berkebutuhan Khusus (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This research explores the correlation between parenting styles and the level of independence among children with special needs attending Special Needs Schools (SLB). Parenting plays a pivotal role in shaping children’s behavioral development and functional abilities, particularly for those requiring more tailored and supportive approaches. Employing a quantitative method with a causal-comparative design, data were obtained through a structured questionnaire distributed to parents of children aged 7–12 with special needs. The results indicate a significant positive correlation between the authoritative (democratic) parenting style and children’s independence. In contrast, authoritarian and permissive styles showed limited influence. These findings underscore the importance of a balanced parenting model that blends guidance with autonomy, as it fosters greater independence in children's daily functioning. The study is expected to contribute to the formulation of family support initiatives and inclusive education policies that strengthen the role of parents as key educators.